ANALISIS IMPLEMENTASI EVALUASI FORMATIF PADA PEMBELAJARAN IPA SMP BERBASIS DISCOVERY LEARNING - Rahmi Nur Salamah; Hendro Prasetyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
21st-century education requires students not only to understand theoretical concepts but also to think critically, creatively, and scientifically. Science learning at the junior high school level plays a strategic role in developing foundational scientific knowledge and process skills. However, conventional teacher-centered learning remains prevalent, limiting active student engagement. This study aims to analyze the implementation of the Discovery Learning method and formative evaluation in science learning, examining its effectiveness, challenges, and supporting factors. A qualitative descriptive approach was employed, collecting data through semi-structured interviews and direct classroom observation. Participants included two science teachers, one school principal, and two students at SMPN 2 Purwakarta. Data were analyzed through reduction, presentation, and conclusion drawing, with source triangulation to ensure validity. Findings indicate that Discovery Learning enhances conceptual understanding, learning motivation, critical thinking skills, and student collaboration. Formative evaluation focused on learning processes enables teachers to authentically assess students’ scientific abilities, while students feel more appreciated and motivated. Key supporting factors include teachers acting as facilitators, students’ enthusiasm, and supportive school policies. Challenges identified include limited time, laboratory resources, and teacher adaptation to the new method. In conclusion, Discovery Learning is effective in creating meaningful, student-centered science learning, but requires adequate teacher training and facilities for optimal implementation.